Aplikasi Mobile dengan Fitur Push Notification Berbasis Android sebagai Media Informasi Pengumuman dan Kegiatan Mahasiswa di Stmik Widya Utama - Sulistiyasni Sulistiyasni; Joko Purnomo; Chandra Bagas Pambudi (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2020)
Widya Utama Institute of Computer and Informatics Management (STMIK Widya Utama) is one of the private universities in the city of Purwokerto which focuses on Information Technology. It seeks to provide services with the availability of information about academic announcements and campus activities that are distributed through bulletin boards and websites. The media has not yet fully become a solution for the availability of up to date and real time information for students. Therefore this study designed Android-based application with a push notification feature as an information media and student activities this campus. This study produces a mobile application that can easily implement the push notification feature and provide information in real time and up to date. This application applies the prototyping method which consists of several steps, namely identifying basic requirements, developing initial prototypes, user reviews, and revice and echance of the prototype. This application is tested using valid value Black Box Testing product and a reliable value benefit tests. From the recapitulation of product test scores and benefit tests, the highest percentage in the Learnability aspect was 98.25%. This means that this application is easily learned by all academic of STMIK Widya Utama